The Anti-inflammatory Effect of Ethanol Extract Gel of Fig Leaves (Ficus carica Linn.) and Sidr Leaves (Ziziphus mauritiana Linn.) - Kurniawan, Muhammad Fariez; Prakoso, Ariffadli; Irawan, Muhammad Indra (Indian Journal of Pharmaceutical Education and Research, 2021)
Inflammation is a form of the body's response to tissue damage with a sign of epidermal thickness, an increase in the number of inflammatory cells and the expression of the COX-2 enzyme. The fig leaves and sidr dry leaves are among the natural ingredients that are used to intervene in inflammation. This study aims to identify the anti-inflammatory effects of ethanol extract of the two natural ingredients formulated in the form of a gel. This study probed 15 groups of research subjects of BALB/c rats (Mus musculus), which were given several treatments. The test parameters were administered on the physical characteristics of gel preparations in the form of organoleptic, pH, spread ability, adhesion and viscosity of the gel as well as anti-inflammatory activity test based on epidermal thickness, a number of inflammatory cells and COX-2 expression. The rats were treated for 3 days before the process of histopathological preparation, Hematoxylin Eosin and COX-2 immunohistochemistry. The results implied that the extracted gel of fig and sidr leaves showed good physical characteristics in the organoleptic, pH 5.73-6.12, 3.29 cm spread ability, 2.98 seconds adhesion and pseudoplastic fluid. The anti-inflammatory activity displayed significant differences in the treatment group, which were 2.5% of sidr leaves extract, 5% of sidr leaves extract, 2.5% of fig leaves extract, 5% of fig leaves extract, 2.5% of fig and sidr leaves extract combination, 5% of fig and sidr leaves extract combination, 2.5% of sidr leaves gel, 5% of sidr leaves gel, 2.5% of fig leaves gel, 5% of fig leaves gel, 2.5% of fig and sidr leaves gel combination and 5% of fig and sidr leaves gel combination compared to negative control. However, when it was juxtaposed with normal and positive control, a conclusion of the treatment group had better activity in reducing the thickness of the epidermis could not be drawn.
Keywords: Anti-inflammatory activity; COX-2 enzyme; Inflammatory cells; Fig leaves; Sidr leaves; Gel